UJI KUALITATIF FORMALIN PADA IKAN ASIN JAMBAL ROTI DI PASAR TRADISIONAL DAN ONLINE KABUPATEN KARAWANG - Hermawan, Yudi; Rismaya, Rina; Fauziyyah, Athiefah; Ulfah, Mutiara (Jurnal Kesehatan Masyarakat, 2023)
As a district that has a fairly large coastal area, Karawang has considerable potential in producing fishery products. One of the leading fish commodities in Karawang Regency is the Manyung fish (Arius thalassinus) which is usually processed into jambal roti salted fish. One of the problems in the traditional processing of jambal roti salted fish is the lack of attention to aspects of sanitation and hygiene, so that the product is easily damaged. Misuse of preservatives from hazardous chemicals such as formalin is still widely found to overcome this problem. This study aimed to identify the presence of formalin content qualitatively in samples of jambal roti salted fish marketed in traditional markets and online markets in Karawang Regency. Jambal roti salted fish samples were obtained randomly (simple random sampling) from traders in five different traditional markets and five samples were obtained from online markets in Karawang Regency. Testing for formalin on salted jambal roti fish was carried out qualitatively using a Test-Kit with two replications. The results of the qualitative formalin test showed that of the 10 samples of salted jambal roti fish tested, none of the samples tested positive for formalin. Thus, the jambal roti salted fish sold in traditional markets and online markets in Karawang Regency tested negative and is free of formaldehyde, so it is safe for consumption.